2014
DOI: 10.1186/1880-6805-33-20
|View full text |Cite
|
Sign up to set email alerts
|

Intake of green tea inhibited increase of salivary chromogranin A after mental task stress loads

Abstract: BackgroundGreen tea has become renowned for its health benefits. In this study, we investigated the anti-stress effect of two kinds of green tea against a mental stress task load.MethodsWarm water, ordinary green tea (Sagara), and shaded white tea, which contains more amino acid components than Sagara, were used as test samples in a randomized cross-over design study. Eighteen students (nine male and nine female) participated in three experimental trials on different days at intervals of seven days. Saliva was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
0
24
1
3
Order By: Relevance
“…Psychological effects measured in terms of VAS score were not significant in our study for any aroma, whereas positive psychological effects are reported in the past with Chocolate [3,4], Green tea [5,6], Apple [7], and Chamomile [12,13]. Chamomile which demonstrated no any significant physiological effect in our study, is reported to have stabilized blood pressure [13] and reduced pulse [14].…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Psychological effects measured in terms of VAS score were not significant in our study for any aroma, whereas positive psychological effects are reported in the past with Chocolate [3,4], Green tea [5,6], Apple [7], and Chamomile [12,13]. Chamomile which demonstrated no any significant physiological effect in our study, is reported to have stabilized blood pressure [13] and reduced pulse [14].…”
Section: Discussioncontrasting
confidence: 40%
“…Green tea demonstrated inhibitory effects on cardiac ANS response. Demonstrating similar effects through endocrinological stress response, green tea inhibited the increase of salivary CgA [6]. Strawberry and Citrus ginger also showed positive physiological effects through inhibiting cardiac ANS response.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Suas medições salivares simples podem ser úteis como uma avaliação objetiva do estresse da pessoa (KANEKO et al, 2017;. Além disso, a atividade desta proteína é passível de aumentar durante as tarefas de cargas estressoras e em situações ansiogênicas, demonstrando sua possível candidatura como biomarcador de curto prazo da carga mental (NOMURA et al, 2010;WAGNER et al, 2010;YOTO et al, 2014).…”
Section: Os Biomarcadores Salivares E Suas Contribuições Para O Diagnunclassified
“…Estudo realizado no Japão apontou associação significativa dos níveis de CgA com situações estressantes de estudantes de enfermagem (TAKATSUJI et al, 2008). Outros estudos demonstraram que houve um aumento da atividade desta proteína durante tarefas de cargas estressoras e em situações ansiogênicas (WAGNER et al, 2010;YOTO et al, 2014). Estes estudos sinalizam que a CgA pode ser um biomarcador para diagnosticar doenças mentais em várias populações, entre elas a de trabalhadores de enfermagem.…”
Section: Introductionunclassified